eCM 2012
DOI: 10.22203/ecm.v023a02
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic differentiation of mesenchymal stem cells is regulated by osteocyte and osteoblast cells in a simplified bone niche

Abstract: Mesenchymal stem cells (MSCs) within their native environment of the stem cell niche in bone receive biochemical stimuli from surrounding cells. These stimuli likely infl uence how MSCs differentiate to become bone precursors. The ability of MSCs to undergo osteogenic differentiation is well established in vitro; however, the role of the natural cues from bone's regulatory cells, osteocytes and osteoblasts in regulating the osteogenic differentiation of MSCs in vivo are unclear. In this study we delineate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
354
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 434 publications
(386 citation statements)
references
References 63 publications
23
354
0
9
Order By: Relevance
“…There were no significant difference for the cell attachment and spreading on the different scaffold groups, which indicated that the additional Bioglass ® didn't effect the cell attachment. However, the 40 wt% Bioglass ® constructs appeared to significantly enhance human ADSCs alkaline phosphatase activity compared with the 5 wt% Bioglass ® and PDLLA only constructs after 4 weeks, suggesting stimulated cell osteogenic differentiation towards the osteogenic lineage as ALP activity has been extensively used as one of the indicators for stem cell osteogenic differentiation (Birmingham et al 2012;Mauney et al 2004). After 6 weeks in vitro culture, Alcian blue/Sirius red staining revealed that extensive collagenous matrix was produced along with the increase of Bioglass ® concentration.…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant difference for the cell attachment and spreading on the different scaffold groups, which indicated that the additional Bioglass ® didn't effect the cell attachment. However, the 40 wt% Bioglass ® constructs appeared to significantly enhance human ADSCs alkaline phosphatase activity compared with the 5 wt% Bioglass ® and PDLLA only constructs after 4 weeks, suggesting stimulated cell osteogenic differentiation towards the osteogenic lineage as ALP activity has been extensively used as one of the indicators for stem cell osteogenic differentiation (Birmingham et al 2012;Mauney et al 2004). After 6 weeks in vitro culture, Alcian blue/Sirius red staining revealed that extensive collagenous matrix was produced along with the increase of Bioglass ® concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The OCM HSPC expansion protocol is based on the differentiation of MSC into immature M-OST after a 6 day osteogenic differentiation period induced in standard osteogenic medium (Birmingham et al 2012). Non-filtered centrifuged supernatant is then frozen without cryoprotectant until use (Dumont et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Results reported by Birmingham et al may shed light into the nonstatistically relevant difference observed in the ALP expression of hASCs, while cultured with Saos-2: the results showed that, in 2D cultures, the transwell-mediated coculture of osteoblasts with mesenchymal stem cells leads to an initial peak in cell proliferation, and a delayed induction of osteogenic differentiation. [30] Another plausible explanation for the results relies in the recently reported ability of tumorogenic cells, namely Saos-2, to prolong hASCs stemness while cultured in direct 2D coculture, as compared to ASCs monocultures. [36] For HUVEC coculture, ALP activity was reduced for half of the value detected on the control condition (M199), as shown in Figure 1c.…”
Section: Resultsmentioning
confidence: 92%
“…Both are known to drive an increased expression of this marker in early time points. [30][31][32][33][34][35] Double stranded DNA (dsDNA) quantification showed that the stem cell spheroids produced in different coculture procedures presented approximately three times more dsDNA than the control conditions (cultured as monocultures in either α-MEM or M199) ( Figure 1c). Similar results were previously reported for other indirect coculture methods, where stem cell proliferation was increased via coculture with osteoblast cells [30,31] and HUVEC cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation